PHYSICAL-CHEMICAL CHARACTERIZATION OF WASTEWATER IN THE CITY OF MISSOUR - MOROCCO. - H. Ech-chafay, M. Najy, N. Bentoutou, M. Lachhab, K. El Kharrim & D. Belghyti (International Journal of Research Science and Management, 2018)
These contaminated and polluted waters are reused directly in the irrigation of parcels with high agricultural activities downstream of the city. They have a negative impact on the environment and can cause illness for both consumers and farm workers. The resolution of this problem requires the establishment of a sewage treatment plant for their reuse without danger in agriculture. The objective of our work is to determine the degree of pollution of wastewater from Missour, based on results obtained by physicochemical analyzes of samples taken from collectors of the city during the period spread between the months of November 2014 and October 2015. The temperature varies between 13 ° C and 26,7 ° C, the pH is about neutral from 7,01 to 7.84. The electrical conductivity from 1963 to 5590 μS/cm, salinity from 1.1 to 3 mg / l, turbidity from 42,1 to 1125NTU, COD Moy = 2066,1 mg / l, BOD5 Moy = 1063,7 mg / l and the TSS Moy = 1739,1 mg / l. Although these waste waters have a high organic load DBO5 / COD = 0,51 ; TSS / BOD5 = 1,63, they have a satisfactory biodegradability. Examination of COD / BOD5 = 1,94 clearly emphasizes the biodegradability of these waters for which biological treatment seems quite suitable. However, account must be taken of domestic wastewater mixed with effluent from the municipal slaughterhouse and effluent from the regional hospital. The values obtained are above the wastewater discharge standards recommended by WHO. At the end of this research, it turned out that wastewater from the city of Missour is of bad quality to very bad.